PEMBINAAN KARAKTER PESERTA DIDIK MELALUI PRINSIP DASAR MANAJEMEN PENDIDIKAN ISLAM - Wahyu Sugiarto; Yuhan Anendi; Farid Setiawan (IAI An Nur Lampung, 2022)
The purpose of this research is to find out how to foster students' character through the basic principles of Islamic education management. In this day and age, there are still many children or adolescents, especially among students whose good character has begun to degrade, this is evident from the many cases that have befallen them such as bullying, drug abuse, free sex, brawls, rape, bullying and many more. Therefore, through the basic principles of Islamic education management it is hoped that it will be a solution in fostering the character of students in accordance with Islamic values. The type of research used is library research through a qualitative approach. The research data sources were obtained through journals, books, articles, theses, and various previous studies. Then the data collection was critically analyzed and presented as a systematic research on the character building of students through the basic principles of Islamic education management. The result of this research is that if you want to foster better student character according to Islamic teachings, educational institutions can apply the basic principles of Islamic management in various educational systems.